Analysis of molecular mechanisms of regenerative processes in tissues of patients with diabetic foot syndrome - O. G. Sarkisyan; V. A. Razdorov; E. V. Andreev; G. Sh. Gafiyatullina (Медицинский вестник Юга России, 2024)
Diabetic foot syndrome (DFS) is a dangerous complication of diabetes mellitus. Despite numerous studies dedicated to the wound healing process in patients with diabetic foot syndrome, surgeries in this pathology are often accompanied by surgical suture failure due to insulin therapy and require repeat surgical intervention. The aim of this study is to analyze the biochemical mechanisms involved in the wound healing process in patients with diabetic foot syndrome. To achieve this goal, articles from foreign databases such as PubMed, MedLine, Google Scholar, and the Russian Index of Scientific Citation (RISC) were selected and analyzed for the period from 2017 to 2023. The search was conducted using keywords such as diabetic foot, wound healing, molecular mechanisms, and their Russian equivalents. A total of 74 publications were identified through the literature search, of which 24 literature sources from 2017 to 2023 were included in the review, corresponding to the direction and purpose of the study. In addition, 18 sources older than 2017 were used to reveal the subject of the study from the references in the literature lists. The literature review discusses various factors that influence the wound healing process: the function of the skin barrier, activity of immune system components, as well as the contribution of hypoxia and endothelial dysfunction to tissue regeneration mechanisms in patients with DFS. Despite the available literature data, it is advisable to search for new factors involved in the development mechanisms of DFS to prevent complications and increase the effectiveness of treatment.